1998
DOI: 10.1002/(sici)1096-9861(19980808)395:3<380::aid-cne8>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the dorsocaudal neostriatal complex: A retrograde and anterograde tracing study in the domestic chick with special emphasis on pathways relevant to imprinting

Abstract: In the forebrain of domestic chicks, a network of distinct regions is crucially involved in auditory and visual filial imprinting. Among these areas, a distinct part of the dorsocaudal neostriatal complex (dNC complex), termed neostriatum dorsocaudale (Ndc), was recently discovered by its enhanced metabolic activity during the presentation of auditory and visual imprinting stimuli. Since there is evidence that the dNC complex consists of several distinct functional subareas, we investigated the neural connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 0 publications
7
71
0
Order By: Relevance
“…Concerning the afferent connection to the IMM, Metzger et al (1998) reported, as a result of retrograde tracing studies, the direct projection from the rostral part of the dorsocaudal nidopallium complex as well as from the mediorostral nidopallium/ hyperpallium ventral. In our study, when the injection was made in the IMM, we also observed retrogradely labeled neurons in the ventral mesopallium and dorsal nidopallium (Fig.…”
Section: Neural Connection Between the Vw And Immmentioning
confidence: 99%
“…Concerning the afferent connection to the IMM, Metzger et al (1998) reported, as a result of retrograde tracing studies, the direct projection from the rostral part of the dorsocaudal nidopallium complex as well as from the mediorostral nidopallium/ hyperpallium ventral. In our study, when the injection was made in the IMM, we also observed retrogradely labeled neurons in the ventral mesopallium and dorsal nidopallium (Fig.…”
Section: Neural Connection Between the Vw And Immmentioning
confidence: 99%
“…The dorsal part of this region appears to be partly coincident with the area described as the neostriatum intermedium pars dorsolateralis (NIDL) in budgerigars (Brauth and McHale, 1988). It also appears to be contained within the broader region corresponding to the dorsocaudal neostriatum (Ndc) in chicken (Metzger et al, 1998) or the dorsal neostriatum (Nd) in pigeon , which receives auditory inputs from fields L1 and L3. In songbirds, Nd is thought to correspond to the shelf region located underneath the song control nucleus HVC (high vocal center; Wild, 1994;Vates et al, 1996;Mello et al, 1998); the shelf in songbirds shows marked ZENK induction in response to hearing conspecific song Jarvis and Nottebohm, 1997).…”
Section: Auditory Regulationmentioning
confidence: 99%
“…10, blue) is probably inherited from a common avian ancestor, because distantly related avian species, such as chickens, doves, pigeons, budgerigars, and songbirds ( Fig. 1), have similar anatomical structures and connectivity (Karten, 1967(Karten, , 1968Kelly and Nottebohm, 1979;Muller and Scheich, 1985;Brauth et al, 1987;Brauth and McHale, 1988;Margoliash, 1992, 1995;Wild et al, 1993;Vates et al, 1996;Metzger et al, 1998;. It has been proposed that in budgerigars the rostral auditory pathway, with Bas as the main telencephalic receiving area, is more important for learned vocal communication than the caudal auditory pathway, which was thought to be more important in songbirds Striedter, 1994).…”
Section: Evolutionary Relevancementioning
confidence: 99%
“…11 An increased Fos expression has also been detected in the same brain area in birds that had performed copulatory behavior in the exact same conditions. 66 Moreover, intermediate hyperstriatum ventrale receives direct input from the neostriatum caudolaterale complex, 68 which is a major target of the belt regions of the visual ectostriatum and of the L1 and L3 auditory field L. 92 Neurons in the intermediate hyperstriatum ventrale have been demonstrated to respond to visual stimuli and are closely associated with learning responses after visual imprinting. 29,31 The increases in glucose uptake observed during the appetitive behavior in both neostriatum caudolaterale and intermediate hyperstriatum ventrale support the notion that their functional connections are excitatory.…”
Section: Somatosensory Telencephalic and Limbic Areasmentioning
confidence: 99%
“…28 This sub-area was termed the neostriatum caudolaterale, and it constitutes a major relay for visual information via afferents from ectostriatal belt. 68 This tertiary multimodal integration is characteristic of the mammalian prefrontal cortex known to mediate complex cognitive operations possibly related to its thalamic afferents. 24,40 The present knowledge is however still not sufficient to firmly establish an homology between these areas in mammals and birds.…”
Section: Somatosensory Telencephalic and Limbic Areasmentioning
confidence: 99%